New Opportunities and Challenges for Health Professionals in the era of Artificial Intelligence – Review - Warchoł, Konrad; Jasiura, Adam; Zając, Marlena; Wójcik, Aleksandra; Giżewska, Kamila (Journal of Education, Health and Sport, 2022)
Introduction and purpose: Modern medical knowledge has grown to a vastness incomprehensible for a single health professional to learn and accommodate. The usage of modern information technologies comes to help, one of them being artificial intelligence, a branch of computer science aimed at developing solutions to perform tasks similar to the human brain, but more efficient and complex, without actual human intervention. The goal of this review is to provide reader with the knowledge how artificial intelligence is applied in various branches of medicine. Brief description of the state of knowledge: In the fields of infectious diseases, including COVID-19 diagnostics, radiology, dermatology and surgery, works lean toward the statement, which suspect application of AI is beneficial for medical practitioners. Programs help to develop statistical models for virus spreading and the creation of antiviral solutions. The radiological application involves the analysis of images to aid radiologists in diagnosing certain features, similarly to dermatology, where eg. AI can identify malignancy of skin nevi. In the department of surgery, predictive algorithms can help in choosing operation methods and improve outcomes. Conclusions: Usage of AI assistance in the medical field has proven to be successful, but it is yet to be commonly encountered in everyday work. Programs need to be further developed and made more approachable to users without expertise in the IT field. AI may also prove useful in the process of education of health professionals.